1999
DOI: 10.1038/sj.cdd.4400561
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 and Bax regulation of apoptosis in germ cells during prenatal oogenesis in the mouse embryo

Abstract: Apoptosis is the main cause of primordial germ cell and oocyte degeneration in the developing fetal ovary. In this study we examined by immunohistochemistry and immunoblotting the expression of the anti-and pro-apoptotic proteins Bcl-2 and Bax in primordial germ cells and fetal oocytes during pre natal oogenesis in the mouse embryo. While Bcl-2 and Bax were not detectable in primordial germ cells in vivo, both proteins were upregulated when they undergo apoptosis in culture. Treatment with the stem cell factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 18 publications
(19 reference statements)
6
69
0
3
Order By: Relevance
“…Oocyte loss and cyst breakdown begin after birth in the cortical region of the ovary, but in the medullary region, these processes begin as early as 17.5 dpc (Pepling et al 2010). This is similar to other studies on the mouse and also on humans where oocyte loss has been observed during fetal development (De Pol et al 1997, De Felici et al 1999, McClellan et al 2003, Ghafari et al 2007). In the rat, follicles are first observed in the core of the ovary and formation gradually shifts toward the surface (Rajah et al 1992).…”
Section: The Process Of Follicular Assemblysupporting
confidence: 76%
“…Oocyte loss and cyst breakdown begin after birth in the cortical region of the ovary, but in the medullary region, these processes begin as early as 17.5 dpc (Pepling et al 2010). This is similar to other studies on the mouse and also on humans where oocyte loss has been observed during fetal development (De Pol et al 1997, De Felici et al 1999, McClellan et al 2003, Ghafari et al 2007). In the rat, follicles are first observed in the core of the ovary and formation gradually shifts toward the surface (Rajah et al 1992).…”
Section: The Process Of Follicular Assemblysupporting
confidence: 76%
“…Deletion of the pro-apoptotic protein BAX yields increased oocyte numbers as primordial follicles in neonatal ovaries when compared with WT (Greenfeld et al 2007). The role of BAX in primordial germ cell, oogonial, and oocyte death is also supported by the observation that BAX expression is upregulated in ovaries during follicular endowment and in cultured fetal oocytes undergoing apoptosis (De Felici et al 1999). BAX expression in oocytes of the human fetal ovary has been detected from the 14th week until term (Vaskivuo et al 2001).…”
Section: Establishment Of the Ovarian Pool Of Primordial Folliclesmentioning
confidence: 50%
“…It has been previously shown that KL and other growth factors (see above) are able to partly prevent apoptosis of primordial germ cells and of isolated and/or ovaryenclosed fetal oocytes as detected by cell morphology and histochemical markers (Pesce et al 1993, Pesce & De Felici 1994, De Felici et al 1999, 2001). Moreover, reported that the rate of oocyte degeneration in cultured embryonic ovaries was not affected by the presence of serum.…”
Section: Caspase Activity In Cultured Oocytesmentioning
confidence: 99%